Tindak Tutur Representatif dalam Video Podcast dengan Tema Kependidikan pada Kanal Youtube Kampus Merdeka - Fitri Nur Wahidiyah; Gea Istifara Noviandini; Nabila Zahra Safanah; Najwa Teta Nur Muharromah; Wafa Khoirunnisa; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Universitas Palan, 2026)
This study aims to examine the forms and functions of representative speech acts in educational-themed video podcasts published on the Kampus Merdeka YouTube channel. This research is grounded in the phenomenon of social media, particularly YouTube, as a means of interactive, participatory communication and learning. In this context, the language used is key to conveying information authentically and responsibly. This study uses a qualitative descriptive method, with data collected through listening and note-taking. The research data consists of utterances containing representative speech acts, such as explaining, stating, informing, mentioning, acknowledging, giving examples, and speculating. Analysis was carried out using the matching method to identify the meaning and function of the utterances based on their context. The results show that representative speech acts play an important role in conveying information and views objectively, as well as strengthening the credibility of the source in the educational context. Through representative speech acts, the message conveyed becomes clearer, more convincing, and more relevant to the topic of discussion. These findings are expected to contribute to the development of effective communication strategies in educational digital media and serve as a reference for educational content creators in the digital era